PENGEMBANGAN MEDIA PASUKAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1 SEKOLAH DASAR: Penelitian Research and Development (R&D) - nadya salsabila; Aqmarina Husnul Bayti; Nina Angraini (STKIP Subang, 2025)
This study aims to develop innovative learning media in the form of PASUKAN (Real Word Board) to improve the reading ability of first grade elementary school students. The background of this study is the low early reading ability of students, which is caused by the lack of learning media that is in accordance with student characteristics. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the study were first grade students of SD Negeri 79 Palembang. Product validation was carried out by media experts, material experts, and practitioners, with an average result of 93.6%, which is categorized as very feasible. Furthermore, product trials were carried out through several stages, namely one-to-one, small group, and field test, with an average result of 96.9%. The validation results show that the PASUKAN media is categorized as very feasible to use. Thus, it can be concluded that the PASUKAN learning media is effective and feasible to use in early reading learning for first grade elementary school students.